2016
DOI: 10.1049/el.2015.2403
|View full text |Cite
|
Sign up to set email alerts
|

Measurement‐based indoor NLoS ToA/RSS range error modelling

Abstract: The time of arrival (ToA) and received signal strength (RSS) estimation errors are modelled based on channel measurements in a non-line-of-sight indoor environment. It is found interesting that their errors are largely independent. Suboptimal hybrid ToA/RSS ranging estimators are derived in closed form based on the obtained error models, and shown to achieve near-optimal performance. The performance of all the estimators improves as the bandwidth increases.Introduction: State-of-the-art ranging systems exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 6 publications
(11 reference statements)
0
37
0
Order By: Relevance
“…Therefore, such an information can be actually provided to the blind node by the i-th transmitting anchor. Although the TOA Model (3) neglects the presence of multipath and the drift of the clocks, it is widely-adopted in different WSN applications and several experiments have shown that it is a reasonable approximation in many cases [40][41][42]52,53].…”
Section: Toa Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, such an information can be actually provided to the blind node by the i-th transmitting anchor. Although the TOA Model (3) neglects the presence of multipath and the drift of the clocks, it is widely-adopted in different WSN applications and several experiments have shown that it is a reasonable approximation in many cases [40][41][42]52,53].…”
Section: Toa Modelmentioning
confidence: 99%
“…It is worth noting that Equation 7represents the actual likelihood under the assumption that both RSS and TOA information are measured from independent sources. Indeed, the experimental campaigns conducted in [52,53] clearly show that measurements extracted from the same signal are weakly correlated; hence, assuming independence in Equation 7is not detrimental to generality. The hybrid TOA/RSS ML estimation problem can be written as:…”
Section: Joint Maximum Likelihood Position Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybrid algorithms based on received signal strength (RSS) and angle of arrival were studied in [1] and [2], but only localization in line-of-sight (LOS) conditions was considered. In [3]- [5] and [7], hybrid algorithms based on RSS and time of arrival (TOA) were presented. Zhang et al [3] and Coluccia and Fascista [4] studied the range estimation problem based on these two quantities, whereas the attention in [5] and [7] was on target localization problem.…”
Section: Introductionmentioning
confidence: 99%